Accelerating the adoption of renewable energy certificate: Insights from a survey of corporate renewable procurement in Singapore. (November 2022) - Li, Peixian; Ng, Jeremy; Lu, Yujie
Abstract: Corporate adoption of renewables has been lukewarm at best in Singapore. This study aims to identify the drivers and barriers to renewable procurement, establish key criteria for renewable energy certificates (RECs, a type of renewable energy product), and recommend policies to accelerate corporate renewable energy adoption in Singapore. We surveyed seven drivers, 12 barriers, nine criteria of RECs, and 11 actions for REC adoption with 35 experienced professionals from major business sectors in Singapore. The top three drivers of corporate renewable procurement were to meet corporate sustainability goals, reduce energy procurement costs, and demonstrate corporate leadership. The most concerning criterion of RECs was traceability that RECs must be generated and transacted through a REC tracking system endorsed by the government or a third party. The most significant barrier to REC adoption was the lack of awareness of RECs and their benefits. Plausible actions to address the barriers include seeking support from senior management, establishing corporate sustainability targets, developing national standards for RECs, promoting successful local business cases, and for government to endorse private-sector REC tracking system(s). The findings could raise corporate awareness and assist policymakers in formulating policies, infrastructure, and initiatives to accelerate renewable energy adoption in Singapore.